Bird Names and Folklore from the Emberá (Chocó) in Darién, Panamá - Kane, Stephanie C. (Ethnobiology Letters, 2015)
This paper presents data on names and folklore of birds collected among native speakers of Emberá in the moist tropical forests of Darién, Panamá. The naming data was collected by systematic elicitation of names from pictorial representations of birds. It is organized here to facilitate analysis of various aspects of folk taxonomy in relation to scientific taxonomy. Folklore about birds collected in natural contexts is also included to indicate the role of birds and their names in symbolic processes that exceed the limits of literal reference.